Evaluating The Potential Benefits Of Permeable Paving Surfaces To Improve Stormwater Runoff Quality - Zan, Sazrul Ariff Mat (Universiti Sains Malaysia, 2022)
Porous asphalt (PA) is an invention that benefited engineers due to the presence of interconnected air voids that allow stormwater runoff to infiltrate through, hence reducing the runoff volume. This reduction helped minimizing lowering the effect of flash flood. This research looked into the potential of porous asphalt as the surface materials. The Public Work Department (PWD) Gradation B was considered in this study. However, some alteration of the gradation based on Dutch PA 16 was carried out and asphalt mixtures samples were prepared to assess the performance. Change in percent passing from 7.5% to 15% at 2.36 mm sieve size showed higher stability value as compared to the original gradation. The upper and lower limits of design binder content for the modified PA gradation range from 4.3 to 5.7%. The stability, abrasion loss, and binder drain down tests results confirmed to the specifications. However, further study is required to improve the air voids content which recorded less than 18% air voids (15.6%) Alternatively, this study also successfully innovates the portable hollow brick maker, which promotes water infiltration through the brick. This man-powered machine used hydraulic press mechanism which required minimum work but greater force output to produce the brick. This study also introduced a laboratory scale water flow simulator. The porous asphalt was used as the surface layer to study the efficiency of a few filtration materials on removing heavy metals which are lead, zinc, copper, cadmium and chromium. The filtration system composed of three alternatives materials which are powdered activated carbon, peat soil and limestone. Each material has been tested on their efficiency on removing heavy metals in the synthetic water after subjected to filtration. Powdered activated carbon has been proven to be the most effective material in removing heavy metals which then followed by limestone and peat soil.